Inferring mechanisms of copy number change from haplotype structures at the human DEFA1A3 locus - Black, Holly A.; Khan, Fayeza F.; Tyson, Jess; Armour, John A.L. (BIOMED, 2014)
Background: The determination of structural haplotypes at copy number variable regions can indicate the mechanisms responsible for changes in copy number, as well as explain the relationship between gene copy number and expression. However, obtaining spatial information at regions displaying extensive copy number variation, such as the DEFA1A3 locus, is complex, because of the difficulty in the phasing and assembly of these regions. The DEFA1A3 locus is intriguing in that it falls within a region of high linkage disequilibrium, despite its high variability in copy number (n = 3–16); hence, the mechanisms responsible for changes in copy number at this locus are unclear. Results: In this study, a region flanking the DEFA1A3 locus was sequenced across 120 independent haplotypes with European ancestry, identifying five common classes of DEFA1A3 haplotype. Assigning DEFA1A3 class to haplotypes within the 1000 Genomes project highlights a significant difference in DEFA1A3 class frequencies between populations with different ancestry. The features of each DEFA1A3 class, for example, the associated DEFA1A3 copy numbers, were initially assessed in a European cohort (n = 599) and replicated in the 1000 Genomes samples, showing within-class similarity, but between-class and between-population differences in the features of the DEFA1A3 locus. Emulsion haplotype fusion-PCR was used to generate 61 structural haplotypes at the DEFA1A3 locus, showing a high within-class similarity in structure. Conclusions: Structural haplotypes across the DEFA1A3 locus indicate that intra-allelic rearrangement is the predominant mechanism responsible for changes in DEFA1A3 copy number, explaining the conservation of linkage disequilibrium across the locus. The identification of common structural haplotypes at the DEFA1A3 locus could aid studies into how DEFA1A3 copy number influences expression, which is currently unclear.